PENGARUH AFILIASI DALAM PEMASARAN DIGITAL DAN DAMPAKNYA TERHADAP PENJUALAN PADA PT SHOPEE INTERNATIONAL INDONESIA - Sahilah, Syahzanan; Sukoco, Iwan; Novel, Nurillah Jamil Achmawati; Barkah, Cecep Safa’atul (LPPM Universitas Multi Data Palembang, 2025)
Abstract: This research investigates the impact of affiliate marketing in digital marketing and its influence on sales at PT Shopee International Indonesia. The aim of this study is to explore the role of affiliate strategies in the context of digital marketing and how these strategies contribute to sales growth. The research adopts a qualitative approach, utilizing literature review, interviews with Shopee users, and sales data from PT Shopee International Indonesia. The findings of this study reveal the significance of the affiliate's role in driving sales and highlight its potential as an effective marketing tool in the digital era. The research concludes by emphasizing the importance of implementing affiliate strategies in digital marketing campaigns to enhance sales performance. Keyword : affiliate, digital marketing,sales, PT Shopee Indonesia